Missionary work in Wonsan - Shigemori Bučar, Chikako (Asian studies, 2025)
In the Cartography Department of the National and University Library (NUK) in Lju-bljana, there is a single picture postcard showing a black and white photo of the Bene-dictine abbey in Tokwon near Wonsan, today’s North Korea. The postcard was printed in Slovenia, or by a Slovenian printing house, because the caption is in Slovene. This picture postcard was not mailed, and there is no additional information regarding who possessed the card and when.In relation to the missionaries posted to Korea during the early twentieth century, it is known that the Vatican divided the Korean region into three, for the French, American and German missionary orders.In the library NUK, there are many similar missionary postcards from other parts of Asia, particularly from India and Ceylon; that is, showing local scenes in relation to missionary works with captions in Slovenian.This paper is a report on further research about the activities of Slovenian missionaries. Was there anybody from the Slovenian region stationed in Tokwon in the 1930s? Or perhaps only the printing of the postcards took place?
Keywords: : Christian missionary; Catholic journals; katoliško časopisje; Korea; Koreja; krščanski misijoni; postcards; razglednice; Slovenia; Slovenija